Effect of ion chelator on pore structure, mechanical property and self-healing capability of seawater exposed mortar. (20th June 2020) - He, Peng; Yu, Jianying; Wang, Ruiyang; Du, Wei; Han, Xiaobin; Gu, Shunjie; Liu, Quantao
Highlights: Ion chelator improves mechanical property of seawater exposed mortar. Compressive strength of mortar under seawater recoveries obviously with ion chelator. Crack of the mortar containing ion chelator under seawater can be healed quickly. Abstract: Ion chelator is a novel crystalline admixture used for improving self-healing capability of cementitious materials. Studies quantifying this self-healing behavior are limited to fresh-water making it unclear under seawater containing magnesium, sulfate and chloride ions. Therefore, the purpose of this paper is to investigate the effects of ion chelator on pore structure, mechanical property and self-healing capability of seawater exposed mortar. The pore size distribution was evaluated by nuclear magnetic resonance (NMR). The self-healing ability was quantified by compressive strength recovery and visible crack closure test, while the composition of crack healing products was analyzed by X-ray diffraction (XRD). The results indicated that ion chelator improves pore structure and compressive strength of mortar under seawater immersion. After 90 days seawater immersion, the proportion of harmful holes (>0.1 μm) in mortar with ion chelator (MCA) was 30.3%, which is lower than in control mortar (CM). The compressive strength of MCA under seawater for 90 days was 34.4 MPa, while that of CM was 27.4 MPa. The ion chelator enhanced the self-healing capability of pre-damaged mortar remarkably. After 28 days seawater immersion, compressive strength recovery rate of MCA under fresh-water and seawater was 94% and 80%, respectively. And the maximum crack width completely healed in MCA under seawater is up to 350 μm, while around 240 μm in MCA under fresh-water. XRD analysis revealed that the crack-healing products in MCA under seawater immersion were magnesium hydroxide and calcium carbonate.